A methodology of manufacturing strategy analysis for the manufacturing industries in Saudi Arabia - Al-Metary, Shwesh Saud Dowaihy. (Cranfield University, 1998)
To further enhance the progress made by its manufacturing industries during the last two decades, the Sixth Development Plan of Saudi Arabia has stressed the importance of diversifying the country’s economic base, reducing its dependence on the production and export of crude oil, and increasing the industrial sector’s contribution to GDP. Since national level industrial policies cannot succeed without the full participation and support of the individual companies, it is necessary for its manufacturing organisations to adopt appropriate methods for increasing their overall competitiveness. This research is concerned with the development of a methodology for manufacturing strategy formulation to help Saudi companies achieve competitiveness in both the local and the international market environment. The work has resulted in a prototype methodology known as MSAMSA - a Methodology of Manufacturing Strategy Analysis for the Manufacturing Industries in Saudi Arabia. The basic concepts of MSAMSA is based on a framework developed previously by the CAMSD research team at Cranfield University, UK. However, the structure and procedures have been further developed to reflect Saudi-specific requirements, and to help link the country’s long-term industrial policy to the medium-term strategic direction of the individual companies. In particular, MSAMSA adopts a generic, extended scheme of manufacturing strategy evaluation, tackling a number of key requirements such as: the need for a more structured way to coherently link strategic policies at different levels, and the need to provide both local- level (internal) and global-level (external) measures to prioritise and evaluate strategic concerns. Industrial case studies have shown that MSAMSA’s approach and compatibility with the current national level policies are both timely and conceptually logical. In addition, these have also highlighted issues which may be of value to the authorities’ future decision-making. Therefore the methodology’s further enhancement and application are anticipated to be of national importance. Due to its generic nature, it should be possible to adopt the extended scheme to satisfy the needs of manufacturing companies within different industrial sectors or even in different countries.